Light-Weight Encryption Schemes for Multimedia Data - BAO, Feng (Institutional Knowledge at Singapore Management University, 2007)
Due to the pervasiveness of high-speed networks and multimedia communications and storage, the demand for highspeed cryptosystems is ever increasing. It is widely believed that there is a tradeoff between speed and security in cryptosystem design. No existing encryption algorithms are both fast enough for high-speed operation and sufficiently secure to withstand powerful cryptanalysis. In this paper, we propose and analyze a generic construction of high-speed encryption schemes. Our solution is based on the fact that there exist secure but relatively slow block ciphers, e. g. AES, and super-fast but relatively weaker stream ciphers. We then combine a secure block cipher with a super-fast stream cipher such that the resulting encryption scheme possesses both the speed of the stream cipher and the security of the block cipher. We show the results our security analysis as well as our experiment on a 2.1 GHz Pentium VI processor.